2010
DOI: 10.1098/rstb.2010.0120
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting phenology under global warming

Abstract: As a consequence of warming temperatures around the world, spring and autumn phenologies have been shifting, with corresponding changes in the length of the growing season. Our understanding of the spatial and interspecific variation of these changes, however, is limited. Not all species are responding similarly, and there is significant spatial variation in responses even within species. This spatial and interspecific variation complicates efforts to predict phenological responses to ongoing climate change, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
146
8
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 62 publications
8
146
8
4
Order By: Relevance
“…The patterns of emergence, abscission and leaf duration are evidently governed by genetic factors, but they are also affected by environmental ones, to which these patterns may be highly sensitive. This has led phenology to become an integral part of studies on climate change and its effects on the vegetation (Ibáñez et al, 2010;Chen & Xu, 2012;Clark et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of emergence, abscission and leaf duration are evidently governed by genetic factors, but they are also affected by environmental ones, to which these patterns may be highly sensitive. This has led phenology to become an integral part of studies on climate change and its effects on the vegetation (Ibáñez et al, 2010;Chen & Xu, 2012;Clark et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ibáñ ez et al 2010; Richardson et al 2010). Observations of life-stage transitions of individual species (Menzel & Fabian 1999;Penuelas & Filella 2001;Ibáñ ez et al 2010) and satellite-based indices of vegetation greenness (Myneni et al 1997;Cleland et al 2007) on land show that spring onset has advanced, autumn senescence has delayed, the growing season has lengthened, and these changes are correlated with rising temperatures in boreal and temperate ecosystems. Terrestrial plants are powerful climate sentinels because their annual cycles of growth, reproduction and senescence are finely tuned to the annual climate cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies reported that spring vegetation phenology is mainly controlled by air temperature in Northeast Asia and on the Tibetan Plateau within which some dry and cold regions exist, but precipitation was not well considered for these dry and cold regions in their studies [4,[8][9][10][11]. As shown in Figures 4 and 5, our study shows that spring phenology of grasslands is mainly controlled by precipitation in Mongolia, particularly by the precipitation of the previous autumn.…”
Section: Dominant Climatic Factor Affecting Sos and Eos Of Dry And Comentioning
confidence: 56%
“…Most observed phenology trends are attributed to air temperature [4,[8][9][10][11]. Theoretically, vegetation phenology is controlled by many factors that differ with climate [2].…”
Section: Introductionmentioning
confidence: 99%